KEBIADABAN MANUSIA DALAM TETRALOGI NOVEL EKA KURNIAWAN KAJIAN STILISSOSIO SASTRA - Sukirno Sukirno (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2020)
The purpose of this study is to describe (1) the use of the language of barbarity, (2) the form of human barbarity, (3) the author's world view on human barbarity, (4) the impact of human barbarity, (5) the way out of human savagery in the novel tetraogy of Eka Kurniawan. This research uses study literature and sociology of literature by using heurmeneutic and mimesis theories to analyze the tetralogy of a novel by Eka Kurniawan. This research uses descriptive qualitative method with a stylistic approach and sociology of literature. The main data of this study are in the form of vocabulary, grammar, and text structure. The results found that many uses of the word vulgar or minority. Found forms of barbarity such as fraud, oppression / torture, quarrels, rape and murder. In the author's worldview, power, deception and suffering are found. The impact of barbarity is found revenge, quarreling and murder. While the way out of savagery can be done by way of education / school, religious, patient and helping each other.